Efektivitas Ekstrak Biji Srikaya (Annona squamosa L.) sebagai Bahan Pembersih Gigi Tiruan terhadap Daya Hambat Pertumbuhan Streptococcus mutans pada Basis Akrilik Heat Cured - Muchammad Fahmi Rizqi Abdillah; FX Ady Soesetijo; Dewi Kristiana (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
The rough surface of a heat cured acrylic resin as a denture base can cause a pathogenic buildup of plaques and biofilms, so an effort to clean the denture base is needed. The available denture cleaning chemicals are proof of some disadvantages, so it is necessary to do research on alternative natural ingredients. Srikaya seed extract using ethanol 96% solvent has been shown to have antibacterial activity and with its various properties, so that it has the potential to become denture cleaning agents. Samples were made based on ADA No.17 specifications with 5 samples in each of the 6 treatment groups, sampling using Simple Random Sampling. Samples contaminated with S. mutans were soaked in srikaya seed extract 25%, 50%, 75%, 100%, 0.5% NaOCl and sterile aquadest. There was a significant difference (p <0.05) in each treatment group. There is an influence of the difference in concentration of srikaya seed extract on the growth of S. mutans bacteria on a heat cured acrylic base. Keywords: heat cured acrylic resin, S.mutans, srikaya seed extract, absorbance